355 First-in-human phase I study of NKTR-255 in patients with relapsed/refractory hematologic malignancies. (10th December 2020) - Shah, Nina; Tan, Alan; Budde, Lihua; Hofmeister, Craig; Cowan, Andrew; Saeed, Hayder; Ye, Jing; Cairo, Mitchell; Rizzieri, David; Orloff, Gregory; Ge, Xue Snow; Lee, Zachary; et al.
Abstract : Background: NKTR-255, an investigational IL-15Rα-dependent polymer-conjugated recombinant human IL-15 (rhIL-15) agonist, maintains the full spectrum of IL-15 biology and provides sustained pharmacodynamic (PD) responses without the need for daily dosing. NKTR-255 engages IL-15Rα and IL-2/IL-15Rβγ leading to natural killer(NK) and CD8 + T-cell expansion, proliferation and activation. In preclinical studies, NKTR-255 enhanced antibody-dependent cellular cytotoxicity(ADCC) of each of daratumumab, rituximab, trastuzumab and cetuximab, resulting in synergistic anticancer activity. This ongoing phase 1 trial(NCT04136756 ) evaluates NKTR-255 in patients with hematologic malignancies. Methods: Heavily pretreated patients with relapsed/refractory multiple myeloma(MM) or non-Hodgkin lymphoma(NHL) received escalating doses of NKTR-255 intravenously q3w. Patients were observed for 3 weeks following the first NKTR-255 dose for dose-limiting toxicity(DLT). Preliminary safety, PK and PD were evaluated in all patients and bone marrow biopsy was evaluated in one patient. NKTR-255-mediated activation of the immune system was assessed by flow cytometry and plasma cytokine analysis. Results: As of June 25, 2020, 4 patients were dosed(1.5µg/kg:3 patients; 3µg/kg:1 patient). NKTR-255 was well tolerated. Most common treatment-related adverse events(AEs): flu-like symptoms, muscle stiffness, and myalgia. One Grade 3 event(pyrexia) was reported, resolving <24 hours with over-the-counter medications. No NKTR-255-related DLTs or serious AEs occurred. Clinical activity was observed in 2/4 patients(NHL and MM). The NHL patient achieved reduced metabolic activity in all prespecified target lesions after 5 cycles. The MM patient achieved stable disease after 3 cycles on NKTR-255 monotherapy. This 63 y/o male had high-risk recurrent stage III MM with complex cytogenetics (relapsing after VRd, DRd, and carfilzomib plus dexamethasone). Preliminary PK analyses(1.5µg/kg) showed mean half-life of >24 hours with no accumulation following repeat dosing. NKTR-255 at 1.5µg/kg expanded NK and CD8 + T-cells in peripheral blood, with peak fold-changes in cell numbers of 5-fold and 3-fold respectively, maintained during the cycle. Bone marrow biopsy data indicate 7-fold(cycle 5) to 13-fold(cycle 9) increase from baseline in the CD56 + population in the MM patient. Proliferative capacity for NK and CD8 + T-cells was maintained across multiple treatment cycles. NKTR-255-dependent changes in inflammatory cytokines, including MCP-1 and IL-6, peaked by 6 hours and resolved to baseline levels by 24 hours, further supporting the safety of NKTR-255. Conclusions: In heavily pretreated patients with hematologic malignancies, NKTR-255 is biologically active and demonstrated sustained increases in NK and CD8 + T-cells. NKTR-255 was well tolerated, with minimal treatment-related toxicities. Our preclinical and preliminary clinical data provide evidence of synergistic effects enhancing ADCC and support continued dose escalation of NKTR-255. Trial Registration: NCT04136756 Ethics Approval: The study was approved by the institutional review board of each participating site.